Holocene environmental history and climate of Ratasjoen, a low-alpine lake in south-central Norway - Velle, G; Larsen, J; Eide, W; Peglar, SM; Birks, HJB (SPRINGER, 2005)
The Holocene environmental history and climate are reconstructed for Ratasjoen, a low- alpine lake in south-central Norway. The reconstructions are based on chironomids, diatoms, pollen, plant macrofossils, and sediment characteristics. From plant macrofossil evidence, birch trees (Betula pubescens) immigrated ca. 10,000 cal BP. The chironomid-inferred mean July air temperature was high, but may be unreliable during the early stages of the lake's history due to the high abundance of Chironomus anthracinus type, a taxon that may include several species. From ca. 9000 cal BP the inferred mean July temperature was lower (ca. 9 degreesC). Temperatures increased towards 8000 cal BP and pine ( Pinus sylvestris) reached its upper limit near the lake. July temperature may have become a significant factor controlling long-term pH in the lake, starting shortly after 8000 cal BP. High pH values were associated with periods of warm summers and lower pH values occurred during periods of colder summers. Alkalinity processes within the lake and/or the catchment are possible factors controlling this relationship. A temperature decline at ca. 5400 cal BP separated two 10.6 degreesC temperature maxima around 6400 and 4500 cal BP. The 1.5 degreesC decline in July air temperatures from ca. 4400 cal BP was paralleled by a decrease of pH from 7.2 to 6.8. Following the temperature drop, first pine and then birch trees declined and disappeared from the catchment and organic accumulation in the lake increased. The increased organic accumulation rate had a positive effect on diatom production. At ca. 2700 cal BP the temperature reached a minimum (ca. 9.2 degreesC) and correspondingly a second pH minimum was reached. Temperature decreased again slightly at ca. 400 cal BP during the 'Little Ice Age', before increasing by about 0.5 degreesC towards the present. Percentage organic carbon as estimated by loss-on-ignition appears to be better correlated with chironomid-inferred July temperatures than organic accumulation rates, at least for the last 9000 years. Accumulation rates of organic sediments are more coupled with catchment-related processes, such as erosion and major changes in vegetation, than is percentage organic carbon.